MUTUAL ACCOMMODATION OF RELIGIOUS DIFFERENCES IN THE WORKPLACE – A JOSTLING OF RIGHTS - Radley Henrico (Obiter, 2021)
In and of itself a constitutional democracy is meaningless. It is the extent to which our rights as individuals in a pluralistic society are given effect and respected that brings to life the constitutionally enshrined values and principles. Religious diversity in a secular society acts as a catalyst of ingredients for conflict in the workplace. Specific legislation has been enacted to give effect to the right against unfair discrimination. Our courts have implemented and interpreted such equality legislation as imposing a duty of accommodation on the employer with regards to the employee’s religion. Our labour-law jurisprudence on transfers of business has recognized a duty offairness that cuts both ways in favour of the employee and employer. In operational requirement exercises the co-operation of both parties is required. In Canada, a duty of mutual accommodation has been utilized in religious discrimination cases. The current duty of accommodation should be extended to include a duty of mutual accommodation given that religious pluralism is a phenomenon affecting both employee and employer, thus enjoining both parties to engage in realistic measures to embrace diversity.